(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2022)
Stereotactic Radiosurgery has been widely utilized for the treatment of intracranial lesions, and this paper presents our experience in treating schwannomas in Bangladesh. This case series was described to present our institutional experience and procedural technique adapted for treating intracranial schwannomas using stereotactic Radiosurgery (SRS) by Linear accelerators. This case series since starting our radiosurgery program in March 2019, we have treated three patients of intracranial schwannoma. Two patients had vestibular schwannoma, and one had Trigeminal Schwannoma. All three patients first underwent surgical intervention and on recurrence/progression treated with stereotactic Radiosurgery. Tumor volume ranged from 4.47 to 10.22 cm3. The dose prescription ranges from 13 to 14Gy in one or two fractions, which was subject to tumor volume, its proximity to a critical structure, existing neurologic deficit, and optimal balance between prescribed dose and predicted complications. All three procedure was free of any immediate adverse event. LINAC based Stereotactic Radiosurgery was found to be a safe and effective option for the treatment of schwannomas. All three patients have a very good clinical outcome, and one patient who has more than one-year post-SRS revealed a significant regression in the size of the tumor. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 181-189